Persistent millennial-scale glacier fluctuations during the last glacial cycle in the southern Tibetan Plateau - Guocheng Dong; Weijian Zhou; Yunchong Fu; Feng Xian; Li Zhang (npj Climate and Atmospheric Science)
Abstract Determining what was responsible for the last glacial millennial-scale glacier fluctuations can help to pinpoint the causes of abrupt climate events during that period. Yet, the question remains poorly constrained in the Tibetan Plateau (TP), where glaciers react to the global climate system via the northern mid-latitude westerlies and Asian Summer Monsoon (ASM). Here, we examine this issue through 10Be exposure dating of moraines in the western Nyainqentanglha Mountains, southern TP. We find that glaciers reached their maximum extent during the last glaciation before the Last Glacial Maximum (LGM), and that the LGM termination pre-dated a rapid CO2 rise at ~18 ka. Changes in summer air temperature, which is tied to the northern tropical Indian Ocean sea surface temperature by the northern mid-latitude westerlies, likely accounted for the pattern of glacial fluctuations, along with the ASM weakening. The rising summer solar insolation from 23 ka also made a positive contribution towards terminating the LGM.